Comparative neuroanatomy of extinct horned turtles (Meiolaniidae) and extant terrestrial turtles (testudinidae), with comments on the palaeobiological implications of selected endocranial features - Paulina Carabajal, Ariana (2017)
Turtles are one of the least explored clades of reptiles with respect to palaeoneuroanatomy. Few detailed descriptions of endocranial features such as the brain morphology or inner ear exist for extant and extinct forms. In this contribution, we present the first CT-based reconstructions of endocranial morphology (brain and inner ear) and the nasal cavities in the terrestrial horned meiolaniid (Meiolaniidae) turtles Niolamia argentina and Gaffneylania auricularis from the Eocene of Patagonia, as well as Meiolania platyceps from the Pleistocene of Lord Howe Island, Australia. In addition, these exclusively Gondwanan Cenozoic taxa are contrasted with cranial endocasts of multiple extant testudinoids, thereby providing the largest sample of digital comparative endocranial data assembled for extinct and living turtles to date. Our study thus adds much needed anatomical information on turtle palaeoneurology. Aspects of meiolaniid palaeobiology are discussed; in particular, the hypertrophied nasal cavity might not to be related to olfactory acuity, but rather perhaps adaptation to arid climatic conditions, and/or intraspecific behaviours.